Effects of Near-Fault Ground Motions on Civil Infrastructure - Nuti, Camillo; Briseghella, Bruno; Lavorato, Davide; Taciroglu, Ertugrul; Bergami, Alessandro Vittorio (Applied sciences, 2023)
Near-fault earthquakes (NFEs), characterized by high peak ground velocity (PGV) and long period pulses, show different properties from far-field ones [...]